Pelanggaran Prinsip Amanah dalam Etika Bisnis Islam: Studi Kasus Rekayasa Laporan Keuangan PT Garuda Indonesia - Ganis Khairulysa Prasetiyo; Laila Barokah; Lina Marlina (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This paper examines the violation of the Islamic business ethics principle of amanah (trustworthiness) through a case study of financial statement manipulation by PT Garuda Indonesia in 2018. The company recorded unrealized revenue of USD 239 million as profit, while in fact it was operating at a loss. This action not only violated accounting standards but also breached Islamic values such as amanah (trust), shiddiq (honesty), and involved elements of tadlis (deception) and gharar (uncertainty). Using a qualitative approach and case study method, this paper analyzes documents from the Financial Services Authority (OJK), the Indonesia Stock Exchange (BEI), and Islamic business ethics literature. The findings reveal that this manipulation caused public distrust, administrative sanctions, and reputational damage. This paper recommends implementing Shariah-based corporate governance, ethical auditing aligned with Islamic principles, and strengthening ethical literacy in the business world. Therefore, justice and accountability in business can be upheld in accordance with Islamic teachings.